STRATEGI PEMASARAN PRODUK BATIK SS DALAM MENINGKATKAN DAYA SAING DI ERA GLOBALISASI - Rahma Nafalina Azzahra; Siti Anisa Almaulani; Lulu ‘Aabidah; Trinindita Nayla Nabila; Abidzar Al Ghifari; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
The Indonesian batik industry must adapt to the demands of globalization and digitalization in order to remain competitive. This study aims to explore the marketing strategies used by Batik SS Pekalongan UMKM in facing these challenges. To study this, a qualitative method with a descriptive approach was applied. Data were collected through in-depth interviews, direct observation, and document analysis from primary and secondary sources. The analysis was carried out by reducing the data, presenting the data, and drawing conclusions. The findings reveal that Batik SS implements flexible marketing strategies, combining traditional methods with digital technology. Product differentiation through glocalization, which integrates Pekalongan motifs with Balinese cultural elements such as barong shirts and daster dresses with “Bali” written on them, is a major strength in attracting tourists. In their traditional strategy, they use direct relational marketing and location-based marketing in Bali's tourist destinations. Since 2024, digital marketing through social media such as Facebook and TikTok, as well as e-commerce platforms such as Shopee Live, has proven to increase online sales, which are higher than offline sales. Despite facing challenges such as price competition in the digital world and the need for content consistency, Batik SS continues to leverage local culture-based innovations and its ability to adapt to modern marketing channels as a basis for improving competitiveness and maintaining business sustainability in the global era.